ENVIRONMENTAL IMPACT OF THE SLATE PLANT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The object of the research is slate production enterprises. To study the environmental impact of the projected enterprise, an environmental review of the state of the environment in the area of construction of the slate production was first carried out. In the results, it was noted that according to the degree of pollution of atmospheric air, soil and groundwater, soil and vegetation cover, the area of the object's location belongs to the zone of an admissible ecological situation. Then an ecological analysis of the design solution was carried out, as well as the types, objects and nature of the enterprise's impact on the environment were studied. During the period of operation, the enterprises the main sources of environmental impact are the asbestos packing and filling unit, cement warehouse, receiving pit and pneumatic transport of cement, boiler room, gas burners. The types of impact are mainly determined by the introduction of cement and asbestos dust, carbon monoxide, nitrogen oxides, iron oxide and manganese oxide into the environment. The results of the study noted that the maximum concentrations of these pollutants abroad of the enterprise will be lower than the quotas established for them. It is noted that the implementation of the project will not lead to negative consequences of the natural environment when the environmental measures and recommendations specified in the work are carried out, as well as when the safety regulations and the operation of the enterprise are observed